MTM-based pharmacist–doctor collaboration and outcomes in type 2 diabetes primary care - Sahat Saragi; Umi Athiyah; Ade Iva Murty (Pharmaciana, 2026)
Medication Therapy Management (MTM) represents a patient-centered pharmaceutical care strategy that necessitates robust interprofessional collaboration, especially between pharmacists and physicians. Within Indonesia's National Health Insurance framework administered by BPJS Kesehatan, healthcare delivery operates through a tiered referral system prioritizing primary care via First-Level Health Facilities (FKTP). The growing emphasis on strengthening primary care engagement and alleviating hospital overcrowding underscores the critical need for optimized health professional collaboration at this level. This study investigated the impact of MTM-based collaborative practice between pharmacists and physicians on clinical outcomes in type 2 diabetes mellitus patients at primary healthcare settings. A quantitative quasi-experimental approach employing a non-randomized pre–post intervention–control design was carried out across FKTP facilities in Central, South, and West Jakarta. Study participants consisted of pharmacist–physician pairs executing MTM-based collaboration alongside type 2 diabetes mellitus patients registered under the Chronic Disease Management Program (PRB). Eight collaborative pairs were established, encompassing 80 patients divided equally into intervention and control groups of 40 each. Measured clinical indicators included Fasting Blood Glucose (FBG), 2-hour Postprandial Glucose (2h-PPG), blood pressure, and total cholesterol, assessed at baseline and following a three-month intervention period. Statistical analysis utilized paired and independent tests based on data distribution, with significance established at p < 0.05. Findings revealed statistically significant improvements across multiple clinical parameters relative to baseline values (p < 0.05), encompassing glycemic indices, blood pressure levels, and lipid profiles. Within the scope of this study's limitations, MTM-driven pharmacist–physician collaboration demonstrated potential in enhancing clinical outcomes for type 2 diabetes mellitus patients in primary care settings. Subsequent research incorporating larger multicenter populations and extended intervention durations is encouraged to assess the long-term sustainability of this collaborative model.